THE ROLE OF COMPETENCE, MOTIVATION AND COMPENSATION IN AFFECTING THE EMPLOYEE PERFORMANCE AT PT. ZTE INDONESIA - Windhi Rakatama, Anggit; Chaerudin, Chaerudin (Dinasti Publisher, 2021)
The decline in employee performance which resulted in work outcomes were less than optimal, that was the moment when a phenomenon occurred. This research aims to assess the impact of competence, motivation and work compensation on employee performance at PT. ZTE Indonesia. The data analysis used multiple linear regression analysis. This type of research was included in quantitative. The sample subjects in this research were 86 employees of PT. ZTE Indonesia. The multiple linear regression analysis result shows if both partially and simultaneously competence, motivation and compensation had significant influence on the employee performance at PT. ZTE Indonesia.